Pricing and static hedging of American-style knock-in options on defaultable stocks - Nunes, J.; Ruas, J.; Dias, J. C. (Journal of Banking and Finance, 2015)
This paper applies the static hedge portfolio approach (SHP) of Chung et al. (2013) in two new directions. First, the SHP approach is generalized from the constant elasticity of variance (CEV) model of Cox (1975) to the jump to default extended CEV (JDCEV) framework of Carr and Linetsky (2006). For this purpose, the recovery value of the American-style down-and-in put is hedged through the one attached to a European-style plain-vanilla contract whereas for an up-and-in put it is necessary to use the recovery component of the corresponding European-style up-and-in option. Second, the SHP methodology is adapted from single to double barrier American-style knock-in options by matching the value of the hedging portfolio along both lower and upper barriers. Finally, and to benchmark the accuracy of the novel SHP pricing solutions, the optimal stopping approach of Nunes (2009) is also extended to price American-style double knock-in options under the JDCEV framework. Such extension highlights the relevant credit derivative component embedded in American-style knock-in equity puts.